1990
DOI: 10.1523/jneurosci.10-03-00814.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term potentiation of small compound and unitary EPSPs at the hippocampal CA3-CA1 synapse

Abstract: Long-term potentiation (LTP) was evaluated for small monosynaptic CA3-mediated EPSPs in CA1 neurons in the guinea pig hippocampal slice. Small EPSPs included those elicited by stimulation of Schaffer axon collaterals of several CA3 neurons (160-480 microV amplitude, n = 40 EPSPs in 40 neurons) and those elicited by stimulation of an individual CA3 neuron (89-563 microV amplitude, n = 14 EPSPs in 11 neurons). Various protocols were employed to induce LTP and were deemed successful as evaluated by recording sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 52 publications
6
10
0
Order By: Relevance
“…LTP of unitary EPSPs could not be induced with high-frequency tetanization of a single CA3 cell in our experiments, consistent with results in ex vivo hippocampal slices (6). The failure of this pattern of presynaptic activity to induce potentiation cannot be attributed to an inability of these synapses to express LTP, as suggested previously (6), because synchronous pairing of the same synapses reliably induced a persistent increase in the unitary EPSP amplitude.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…LTP of unitary EPSPs could not be induced with high-frequency tetanization of a single CA3 cell in our experiments, consistent with results in ex vivo hippocampal slices (6). The failure of this pattern of presynaptic activity to induce potentiation cannot be attributed to an inability of these synapses to express LTP, as suggested previously (6), because synchronous pairing of the same synapses reliably induced a persistent increase in the unitary EPSP amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Potentiation of these compound EPSPs persisting >4 min was only obtained when the compound EPSP had an amplitude >4 mV. Previously reported data from ex vivo hippocampal slices are consistent with-this conclusion (4,6). Unitary Schaffer collateral EPSPs in hippocampal slice cultures have a mean amplitude of -1 mV (13).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This hypothesis is supported by the observation that, following the induction of LTP and subsequent pharmacological blockade of AMPA receptors, the residual NMDA receptor-mediated component of synaptic responses shows only a small magnitude of potentiation compared with that exhibited by the AMPA receptor-mediated component. This finding is consistent with the supposition that NMDA receptor binding in the synapse is near saturation during each release of transmitter as a result of the high affinity of the receptor for glutamate (Herron et al 1986;Harris and Cotman 1986;Friedlander et al 1990;Grover and Teyler 1990;Zalutsky and Nicoll 1990). More recently, however, the view that LTP expression is mediated exclusively by changes in AMPA receptors has been challenged by us and other who have demonstrated that the NMDA component can express LTP with a magnitude equivalent to that expressed by the AMPA component (Xie et al 1992a,b;O'Connor et al 1995).…”
Section: Introductionsupporting
confidence: 91%
“…We compared how the parameter estimates depend on stimulus voltage to ascertain that the vesicular dynamics are not affected by the interactions between collaterals or boutons. This is relevant because at guinea pig CA3-CA1 synapses, the induction of LTP depends on how many synapses are stimulated (Friedlander et al 1990). The initial EPSC amplitudes expectedly increase with greater stimulus voltage (Fig.…”
Section: How the Parameters Of A Two Pool Vesicular System Affect Synmentioning
confidence: 99%